PWE-133 Female Representation in Leadership Roles: Results from The Supporting Women in Gastroenterology (SWIG) Survey. (17th August 2016) - Arthurs, E; Brooks, A; Taylor, E; Solomon, J; Neild, P; Thomas-Gibson, S; Lockett, M; Edwards, C; Eaden, J
Abstract : Introduction: Whilst numbers are increasing, women remain under-represented at both trainee and consultant grade in gastroenterology compared with other medical specialties, 52% and 34% respectively. 1 There is little available data on female representation in leadership roles in gastroenterology in the UK. The aim of this survey was to identify the key issues around female representation in positions of leadership. Methods: A comprehensive survey was designed and circulated to consultants and trainees in gastroenterology; all were members of the BSG. Data regarding demographics, professional experiences and opinions was collected and analysed. Results: The survey was sent to 1900 people, 600 people opened the email and 186 responded, a response rate of 9.79%. 107 of respondents were female (62.9%), 16 respondents did not declare gender. Data was available for 183 responses. Of 188 responses, 119 (63.3%) of respondents had a leadership role; 66 were female (55.5%) and 52 (43.7%) were male. 48 (40.3%) had a local role within the medical school, LETB or NHS trust (29 (60.4%) female versus 18 (37.5%) male); 40 (33.6%) had one or more regional roles (23 (57.5%) female versus 17 (42.5%) male) and 31 (26.1%) had one or more national roles (14 (45.2%) female versus 17 (54.8%) male). Important reasons for not having a leadership role were time constraints due to workload at work (22.4% of responses, n = 32, 75% female versus 21.9% male (gender not declared 1)), time constraints due to home commitments (18.2% of responses, n = 26, 80.8% female versus 19.2% male) and lack of confidence (14.7% of responses, n = 21, 80.9% female versus 19.0% male). Iimportant factors to encourage people to take on a leadership role included time and flexibility at work (30.4% of responses; n = 49, 77.6% female versus 22.4% male), personal invitation (24.2%; n = 39, 82.1% female versus 17.9% male) and more opportunity (11.9%; n = 18, 77.8% female versus 22.2% male). Conclusion: Whilst women hold local and regional leadership roles, they remain under-represented at nationally. Strong influencing factors that have emerged are busy work and home commitments and lack of confidence. Introducing more time and flexibility into job roles, personally inviting potential female candidates and creating more opportunities may encourage more women in the speciality to undertake leadership roles. Reference: 1 Census of consultant physicians and higher speciality trainees in the UK, 2014–2015. Royal College of Physicians, 2016. Disclosure of Interest: None Declared